Pengaruh Tingkat Pendidikan terhadap Kualitas Kinerja Aparatur Desa Kacangan Kecamatan Tambakrejo Kabupaten Bojonegoro - Akmal Bhagaskara; Fitrotun Niswah; Meirinawati Meirinawati; Eva Hany Fanida (Journal of Legal, Political, and Humanistic Inquiry, 2026)
This study examines the influence of education level on the quality of performance of village apparatus in Kacangan Village, Tambakrejo District, Bojonegoro Regency. The research employs a quantitative approach using primary data collected from respondents through structured questionnaires. Data analysis was conducted using descriptive statistics and inferential analysis, including simple and multiple linear regression tests. The results indicate that the education level of village apparatus has a positive and significant effect on overall performance quality, particularly on the productivity dimension. The coefficient of determination shows that education level explains a substantial proportion of performance variation among village apparatus. However, further analysis reveals that education level does not significantly affect other performance dimensions, namely service quality, responsiveness, responsibility, and accountability. These findings suggest that formal education alone is insufficient to enhance all aspects of village apparatus performance. Organizational systems, work experience, leadership, and institutional control mechanisms play a critical role in shaping service-oriented and accountable performance. Therefore, improving village governance requires an integrated approach that combines education with continuous training and effective organizational management.